The Influence of Product Quality and Price Perception on Purchase Decision: Satisfaction as A Moderation - Syofika Handayani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2023)
This study examines the influence of product quality and price perception influence purchasing decisions, with satisfaction as a moderating variable at PT. Pariaman Iced Tea. Methods of data collection through surveys and distributing questionnaires, with a sample of 100 respondents. The analytical method used is SEM analysis using smartpls. The research results based on hypothesis testing showed a significant influence of product quality on purchasing decisions. There is a significant influence of price perceptions on purchasing decisions. There is no significant effect of product quality on purchasing decisions which is moderated by satisfaction. There is no significant effect of perceived price on purchasing decisions which is moderated by satisfaction.